Changes in salinity and sediment supply in Laguna de Bay during the past 6,000 years - Jaraula, Caroline Marie B. (2001)
Salinity shifts within Laguna de Bay were derived through the identification of molluscan and diatom assemblages of a compound core taken from the western lobe of Laguna de Bay. The deepest samples yield mostly brackish water Thiara sp. and the low-salinity tolerant marine Tellina sp. and Leptaxinus sp. By 5,740 yBP only marine shells, with the addition of Anomalocardia sp.,predominated. Marine diatoms, such as Cyclotella stylorim, Thalassiosira eccentrica and Thalassiosira lineata, comprise 80 percent of the diatom population. The mollusk and diatom assemblages reveal a lagoonal environment with depths initially greater than 10 m during a relatively higher than present sea level in the south and southeast Asia. Overtopping the present-day 30 meter high barrier between the lake and Manila Bay by the sea level rise to produce the marine signature is impossible. Alternatively, with the barrier submerged , uplift from the adjacent West Marikina Valley Fault in the last 6, 000 years would have raised a sill that would eventually block the lake from Manila Bay. Shallowing brought about by movements from this fault and sea level fall for the next 1, 800 years, resulted in change in the water to brackish, and eventually to freshwater. The occurence of brackish water limit is placed at 3,000 yBP, when only 4 percent of the marine shells remained and freshwater diatoms rose to 90 percent. The causes of the salinity shifts were established through historical geochemical signatures. From these geochemical proxy records, the salinity indices show a step-like decrease to freshwater levels, which is correlated to the episodic uplift of the barrier at 250-year intervals. Paleosalinity shifts had affected the sediment quality and the productivity in the lake. Fresh to brackish water conditions yields high primary production. In a shorter term, each shift imposed stress on the lake fauna and was accompanied by a decrease in diatom concentration, mass mortality, and dwarfing of mollusks. Geochemical proxy records of lake productivity, such as total diatomcounts, total organic carbon and biogenic silica anti-correlate wit increases in sediment supply. The resulting deposits fluctuated from extra-basinal clastics to intra-basinal organic matter or a mixture of both. The average sedimentation rate excluding the past several tens of years, the highest sedimentation rate at 1.37 cm/yr is exhibited during the interval 5,700 to 5,600 yBP. This high sedimentation rate is accompanied by significant changes in the concentration of all the metals, showing slight changes in the concentration ratios of conservative elements, such as Ti/Al. Furthermore, the Chemical Index of Alteration {(Al/(Al+Ca+Na+K))x100] and Rb(ppm)/K(%) ratios indicate a long-term shift from a highly weathered to a slightly weathered condition, suggesting an introduction to a geochemically new source material. This paleoenvironmental shift may be related to the latest caldera-forming eruption of Taal Volcano. Slight shifts in the Ti/Al ratio upcore are correlated with possible changes in the relative amounts of sediment contributions from defferent sub-watersheds. The decrease of Ti/Al values at the uppermost levels is correlated with saltwater backflows into the lake and the opening of the Manggahan Floodway. Both mechanisms introduce new sources of deposits that are relatively depleted in Ti and enriched in Al.